Experimental Test of Hydram Pump Model in Utilization of Artesian Well Water Flow - Samsul Arifin; Bahrul Ulum; M. Fathuddin Nur (UNIPA PRESS, 2022)
A hydraulic ram is a device for moving fluid from a lower place to a higher place. Hydram pumps have the same function as pumps in general. The driving energy of the hydraulic ram pump comes from the pressure of the water entering through the suction pipe into the pump. By using the energy of a large enough flow of water at a low place, the water will flow to a higher place with less water flow capacity. The capacity of water flowing to a higher place depends on the difference in pressure between the suction pipe and the pump discharge pipe. The design of the hydraulic ram pump in the form of a model is used to distribute water sourced from artesian wells. The calculation results show that the maximum pump capacity of 2.11 x 10-4 m3/s occurs at the suction valve opening 90° and the discharge valve opening 90°, and the minimum capacity 0.51x10-4 m3/s occurs at the suction valve opening 90° and the discharge valve opening 20 °. The maximum pump head of 4.34 m occurs at 90° suction valve opening and 90° discharge valve opening, and the minimum 1.33 m pump head occurs at 90° suction valve opening and 20° discharge valve opening. The maximum water power of 0.0119 Hp occurs at 90° suction valve opening and 90° discharge valve opening, and the minimum water power occurs at 90° suction valve opening and 20° discharge valve opening.